Yield of Screening for TB and HIV among Children Failing to Thrive in Botswana. (27th August 2013) - Arscott-Mills, Tonya; Ho-Foster, Ari; Lowenstein, Margaret; Jibril, Haruna; Masunge, Japhter; Mweemba, Phanuel; Nashara, Paul; Makombe, Robert; Chirenda, Joconiah; Friedman, Harvey M.; Steenhoff, Andrew P.; Harari, Nurit
Abstract: Background: Failure to thrive (FTT) is a sign of tuberculosis (TB) and human immunodeficiency virus (HIV) infection. We assessed TB and HIV prevalence in children with FTT at one clinic in Botswana. Methods: In July 2010, we screened all children attending a 'Well Child' clinic for FTT. Children with FTT were referred to a paediatrician who: (i) assessed causes of FTT, (ii) evaluated for HIV and TB and (iii) reviewed the patient chart for evaluations for TB and HIV. Results: Of 919 children screened, 176 (19%) had FTT. One hundred eighteen (67%) children saw a paediatrician, and of these, 95 (81%) completed the TB evaluation. TB was newly diagnosed in 6 of 95 (6%). At review, HIV status was known in 23 of 118 (19%). Ninety-five had an unknown HIV status. Forty-five (47%) tested for HIV; all tested HIV-negative. Conclusion: TB and HIV screening among children with FTT diagnosed TB in 6% of cases completing an evaluation, but no new HIV infections.